PENGARUH LATIHAN DRILL TERHADAP KETEPATAN PENERIMAAN BOLA PERTAMA DALAM PERMAINAN BOLA VOLI DI EKSTRAKULIKULER SMAN 1 KADUGEDE - Ismira Inaya Wulandari (Journal of Physical Education and Sport Science, 2023)
Ismira Inaya Wulandari (NIM 182223167). Health and Recreation Physical Education Study Program, 2022, page. This study uses experimental research methods, with a pre-experimental research design. The samples used in this study were members of the volleyball extracurricular at SMAN 1 Kadugede, totaling 17 people. In this study, the instrument uses a wall bouce training model (down passing drill using a wall). The final product of the wall bouce training model is the accuracy of receiving the first ball in volleyball. The results of this study are data about the pretest and posttest scores using the SPSS 25 program with a significant level of 0.05. The results of this study indicate that the average value of the pretest is 4.94 and the posttest is 6.85. With the hash value of the t-test test is 0.000 which means > 0.05, which means that there is a significant effect of the given exercise program. From the research that has been done, it can be concluded that the drill training model can be developed and applied in the training process. Keywords : Accuracy, Drill, First Ball